FEA-Based Thermo-Structural Modeling of Cryogenic Storage Tanks in Liquid Propulsion Systems - Salvador Orozco; Cynthia L. Ramirez Zamora; Md Amzad Hossain; Ahsan Choudhuri (Aerospace, 2025)
This investigation presents the comprehensive thermo-structural analysis of the propellant tanks utilized in the CROME propulsion system, focused on examining the structural effects caused by the storage of liquid nitrogen, liquid oxygen, and liquid methane. These fluids operate at extremely low temperatures and generate large thermal stress gradients in the tanks, significantly influencing their structural properties. For this reason, it is of vital importance to inspect the generation of mechanical and thermal stresses in the tanks to assess the risk of structural failure. To accomplish this effort, this analysis evaluates the tanks containing liquid nitrogen, liquid oxygen, and liquid methane at pressures of 200.0 psi and 400.0 psi. A coupled finite element analysis was performed in Star-CCM+ to compute the resulting Von Mises stresses under steady-state conditions. These stress results were used to determine the factor of safety in each case, enabling a quantitative assessment of structural integrity in the tanks while operating with cryogenic fluids under different pressure loadings.